Micromap plots to visualize air pollution at national and local level in Korea. Issue 2 (3rd March 2016) - Ahn, Jeong Yong
Abstract : Air pollution is a persistent and pervasive environmental problem with health implications and economic costs for society. In this study, we introduce a new approach for visualizing air pollution data and describe how spatial patterns of air pollutants can be examined simultaneously using linked micromap plots. To explore the potential utility of the plots, we analysed and visualized Korean air pollution data for the period 1989–2012 at national and local level. Our analysis revealed that sulphur dioxide (SO2 ), fine particle and carbon monoxide decreased for the period, but ozone increased uniquely. The pollution level of Jeju was lowest. Daegu and Gyeonggi showed the highest levels. Daegu had highest values in both range and interquartile range. SO2 decreased the most in Gangwon which had formerly had the largest number of coal mines. Regions with high levels of fine particles were located mainly in the northwest, probably influenced by dust, and in the southeast, industrialized areas.